99mTc-HYNIC-MPG: A novel SPECT probe for targeting mutated EGFR. Issue 7 (1st April 2015) - Yan, Yan; Xiao, Zun-Yu; Song, Yan; Kang, Zhao-Ting; Wang, Ping; Sun, Xi-Lin; Shen, Bao-Zhong
Graphical abstract: Abstract: Mutated epidermal growth factor receptor (EGFR) is an important biomarker for cancer diagnosis and molecular target for many anticancer drugs. Localizing EGFR and evaluating EGFR mutational status can help to identify patients who are potentially the most suitable ones for targeted treatments. Hence, we developed a novel EGFR tyrosine kinase inhibitor labeled with 99m Tc ( 99m Tc-HYNIC-MPG) and evaluated its EGFR binding capacity in vitro and in vivo. This molecular probe was synthesized by one-step method that is simple and highly efficient. Importantly, the uptake rate for 99m Tc-HYNIC-MPG in the liver was as low as 28.44 ± 0.15% (mean ± SD, n  = 3). This finding presents for the first time that 99m Tc-HYNIC-MPG can bind to mutated EGFR efficiently and thus provides a novel molecular tool to detect mutated EGFR and suppress tumorigenesis.